ChemInform Abstract: Palladium‐Catalyzed Cross‐Coupling of Benzyl Chlorides with Cyclopropanol‐Derived Ketone Homoenolates. Issue 18 (May 2015) - Nithiy, Nisha; Orellana, Arturo
Abstract The scalable method delivers good reaction yields using various cyclopropanols and electron‐rich or electron‐neutral benzyl chloride.